2015
DOI: 10.1186/s12886-015-0126-8
|View full text |Cite
|
Sign up to set email alerts
|

Central retinal artery occlusion associated with persistent truncus arteriosus and single atrium: a case report

Abstract: BackgroundCentral retinal artery occlusion (CRAO) is an ocular emergency and most of the cases present with painless sudden persistent loss of vision in the range of counting fingers to perception of light. The presentation of CRAO is associated with a variety of medical conditions. We report a rare case of CRAO associated with persistent truncus arteriosus (PTA) and single atrium in a female patient.Case presentationA 23-year-old woman was admitted due to sudden painless visual loss in the left eye. On examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The aetiology of RAO includes thrombosis, embolus, arteritis, vasospasm [ 4 ]. Clinically, the consequences of this vascular accident are dramatic, and delayed treatment may cause blindness; RAO is more common in hypertensive arteriosclerosis patients and occurs occasionally patients with endocarditis [ 5 , 6 ]. Visual loss is a major symptom in CRAO, while limited vision field has been described in BRAO.…”
Section: Introductionmentioning
confidence: 99%
“…The aetiology of RAO includes thrombosis, embolus, arteritis, vasospasm [ 4 ]. Clinically, the consequences of this vascular accident are dramatic, and delayed treatment may cause blindness; RAO is more common in hypertensive arteriosclerosis patients and occurs occasionally patients with endocarditis [ 5 , 6 ]. Visual loss is a major symptom in CRAO, while limited vision field has been described in BRAO.…”
Section: Introductionmentioning
confidence: 99%
“…rt-PA is approved by American Food and Drug Administration and is the only one attested by a large number of clinical experiments in European and American countries ( 23 ). As a thrombolytic drug recommended for use to treat ischemic stroke, it can be administered through arteries or veins.…”
Section: Discussionmentioning
confidence: 99%
“…Curative effects could be classified into four levels on the basis of the situations of visual acuity, fundus oculi and visual field as: cured, markedly effective, effective and ineffective, respectively. Cured indicated that the visual acuity improved by 4 lines or more in the logarithmic visual acuity chart or the visual acuity improved by less than 4.8; no edema existed in the retina of fundus oculi; and the scope of visual field defect reduced by >50% or the visual field returns to normal on the whole ( 2 , 21 , 23 25 ). Markedly effective indicated that the visual acuity improved by >3 lines; ischemia of fundus oculi improved basically, and the scope of visual field defect decreased by 30–40%.…”
Section: Methodsmentioning
confidence: 99%
“…Young-onset CRAO is related with a number of medical disorders, such as hyperhomocysteinemia, temporal arteritis, SLE, sickle cell disease, platelet-aggregation abnormalities, and migraine headaches, among others. 41 In contrast, cardiogenic emboli are a very rare cause of CRAO, accounting for only 1% of all cases. In spite of the fact that atrial fibrillation and left ventricular dysfunction are the most common cardiac causes of congestive heart failure, extracardiac factors (mainly aortic and carotid plaques) have been proven to be related with this illness in the great majority of instances.…”
Section: Crao In Young Populationmentioning
confidence: 99%